INFLUENCES FROM THE EAST ON THE HELLENISTIC POTTERY FROM BUDVA FROM THE GREEK COLLECTION OF THE NATIONAL MUSEUM IN BELGRADE - Krstić, Vera (Rei Cretariae Romanae Fautorum Acta, 2024)
Back in 1937, when the foundations for the hotel “Avala” were being dug in Budva, a necropolis with three levels was unearthed. The uppermost and the middle levels contained cremation burials belonging to the Roman period while the lowest contained inhumations dated to the 3rd–1st centuries BC.2 The cremated remains from the poor graves had been placed in clay urns, while those from the richer graves had glass urns instead, which were protected additionally by cylindrical stone urns with lids. The remains in the graves of the lowest horizon were usually buried separately (graves with two skeletons were rare), either in a constructed grave or in a sarcophagus. The grave finds from the inhumation burials included bronze weapons along with a small number of ceramics for everyday use, which could be dated to the earliest phase of settlement in Budva, the 6th–5th centuries BC. However, we have more information about the next phase of the necropolis from the period between the 3rd and the 2nd century BC. These finds belong to the period of the classical Illyrian state and the rise of Budva before it was conquered by Romans, which brought the final prevalence of Roman elements in the material culture of this region.